Al-Jaya Palace and the New Shawbak Town. A Medieval frontier and the return of the urbanism in the Southern Transjordan - Guido Vannini (Ksiegarnia Akademicka Publishing, 2020)
Al-Jaya Palace and the New Shawbak Town. A Medieval frontier and the return of the urbanism in the Southern Transjordan